Effect Of Plyometric Training On The Development Of Physical Fitness Among Hyderabad Athletes (International Journal of Food and Nutritional Sciences, 2022)
The Fitness is the ability of an individual to live a full and balanced life. It involves physical, mental, emotional, social and spiritual factors and a capacity for their wholesome expression.” Participation in daily physical activities results in the proper growth and maintenance of good health. Running, jumping, throwing, climbing and hanging from the basic pattern of motor movements throughout the life of human beings; The purpose of the study was to find out the effect of plyometric training whether or not any significant difference found between pre-test and post-test of selected physical fitness variables on Athletes of men and their performance. Hypothesis:There may not be any significant difference between pre – test and post on effect of Plyometric training program among men Hyderabad athletes in relation to physical fitness variable. Methods and Materials: